2020
DOI: 10.2139/ssrn.3697402
|View full text |Cite
|
Sign up to set email alerts
|

Public Procurement in Law and Practice

Abstract: The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research.At least one co-author has disclosed a financial relationship of potential relevance for this research. Further information is available online at http://www.nber.org/papers/w27188.ack NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subject to the review by the NBER Board of Directors that accompanies official NB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 12 publications
2
30
0
1
Order By: Relevance
“…Finally, the decree does not a↵ect parties' intentions to appeal court decisions. Taken together, these results contribute court-level causal evidence on the role of legal reforms in strengthening institutions, complementing and extending a literature that has relied on cross-country and within-country evidence (Djankov et al, 2003;La Porta et al, 2008;Chemin, 2018;Bosio et al, 2020).…”
Section: Introductionsupporting
confidence: 62%
“…Finally, the decree does not a↵ect parties' intentions to appeal court decisions. Taken together, these results contribute court-level causal evidence on the role of legal reforms in strengthening institutions, complementing and extending a literature that has relied on cross-country and within-country evidence (Djankov et al, 2003;La Porta et al, 2008;Chemin, 2018;Bosio et al, 2020).…”
Section: Introductionsupporting
confidence: 62%
“…Ferraz et al, 2015;Smith, 2017;Gugler et al, 2020). Alternatively, selection might be explained with superb information driven by political connections and favouritism (Bosio et al, 2020;Baltrunaite, 2020), which could then ambiguously confound the PPC effect downward if such connections can impose high mark-ups for construction works or to low productive firms with substantial organizational slack. Conversely, it could confound the PPC effect upward if the political connections open up more opportunities than just the PPC, e.g.…”
Section: Identification Strategymentioning
confidence: 99%
“…However, even though these procedures exist, their outcomes are rather heterogeneous. A recent macro-level study on a sample of 187 countries found a positive association between perceived country-level corruption and unfavourable procurement processes and outcomes (Bosio et al, 2020). Along this line, at the micro-level, Vuković (2020) suggests PPCs as a tool to buy votes and build a crony winning coalition, Lehne et al (2018) show politicians can adjust resource allocation in favour of their family members at a great cost to the society, while Andreyanov et al (2017) and Baltrunaite (2020) suggest resource allocation 1 Link: https://blogs.worldbank.org/developmenttalk/how-large-publicprocurement [Accessed 15th February 2021.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is to our knowledge the first attempt to investigate how exogenous variation in individual firms' ability to access a particular market affects their growth. The source of demand we focus on-buyers that purchase goods and services through tenders and other formal contracts-is an especially important one: public procurement alone makes up roughly 12 percent of worldwide GDP and more in low-income countries (Bosio et al, 2020). Our analysis begins to characterize how limited marketing ability and its interaction with more widely studied forms of information frictions excludes productive suppliers from growth opportunities.…”
Section: Introductionmentioning
confidence: 99%